2020
DOI: 10.1101/2020.03.24.005512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for a growth zone for deep subsurface microbial clades in near-surface anoxic sediments

Abstract: Global marine sediments harbor a large and highly diverse microbial biosphere, but the 1 2 mechanism by which this biosphere is established during sediment burial is largely 1 3 unknown. During burial in marine sediments, concentrations of easily-metabolized 1 4 organic compounds and total microbial cell abundance decrease steadily. However, it is 1 5 unknown whether some microbial clades increase with depth, despite the overall trend of 1 6 abundance decrease. We show total population increases in 38 microbia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Similar to the procedure described by Lloyd et al . ( 2020 ), we normalized the fractional abundance of the Chloroflexi 16S rRNA abundance to quantitative values using the qPCR determined 16S rRNA gene concentrations as described previously (Vuillemin et al . 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the procedure described by Lloyd et al . ( 2020 ), we normalized the fractional abundance of the Chloroflexi 16S rRNA abundance to quantitative values using the qPCR determined 16S rRNA gene concentrations as described previously (Vuillemin et al . 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to a protocol for quantitative normalization of barcoded 16S gene sequence data ( 24 ), we normalized group-specific 16S rRNA gene abundances by dividing the total number of 16S rRNA gene copies determined via quantitative PCR (qPCR) by their affiliated 16S rRNA gene relative abundances (fractional percentage of total sequences per sample). This showed that “ Ca .…”
Section: Resultsmentioning
confidence: 99%
“…At oxic site 12, our limit of detection (10 2 × 16S rRNA gene copies per DNA extraction) is reached at ~8 mbsf, whereas at oxic site 11, the density of 16S rRNA genes increases by two orders of magnitude at ~6 mbsf before reaching the detection limit at 15 mbsf. Similar to the procedure described by Lloyd et al (2020), we normalized the fractional abundance of the Chloroflexi 16S rRNA abundance to quantitative values using the qPCR determined 16S rRNA gene concentrations as described previously (Vuillemin et al, 2019). The 16S rRNA gene density of Chloroflexi at both oxic sites sampled decreases constantly with depth, reaching the limit of detection at 15 mbsf at site 11 and at mbsf at site 12.…”
Section: Diversity Density and Taxonomy Of 16s Rrna Genesmentioning
confidence: 99%